2021
DOI: 10.3390/life11111195
|View full text |Cite
|
Sign up to set email alerts
|

Direct Current Electrical Fields Improve Experimental Wound Healing by Activation of Cytokine Secretion and Erk1/2 Pathway Stimulation

Abstract: There is growing evidence that cell behaviors can be influenced by the direct current electric fields (EFs). Some behaviors may influence wound healing directly. This study aimed to investigate the effects of EF (200 mV/mm) on immortalized nontumorigenic human epidermal (HaCaT) cells. We established a setup that can transmit an EF and maintain a stable cell culture environment. An EF was applied to HaCaT cells, and scratch-assays were performed as a model of wound healing to observe cell migration. Proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 53 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…The setup to transmit the MC signal was as described previously [ 15 ]. In short, a custom-made 6-well plate containing four identical electrotactic chambers was used to build the setup.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The setup to transmit the MC signal was as described previously [ 15 ]. In short, a custom-made 6-well plate containing four identical electrotactic chambers was used to build the setup.…”
Section: Methodsmentioning
confidence: 99%
“…Treatments to accelerate wound healing and cure chronic wounds are actively sought, and one non-invasive and convenient treatment, electrical stimulation (ES), has been used successfully in research for clinical applications [ 11 ]. Based on the existence of endogenous electrical fields at human wound sites (created by the transepithelial potential difference (TEP)) [ 12 ], researchers have shown that electrical signals are crucial initiators and regulators of wound cell proliferation [ 13 ], migration [ 14 ], secretion function [ 15 ] and, therefore, act to accelerate wound closure [ 16 ]. Microcurrent (MC) is “an electrotherapeutic modality that uses low levels of electrical current (less than 1 mA) to facilitate circulation and cellular healing or to reduce pain or edema” [ 17 ]; it is an electrotherapy strategy involving microampere range current [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The publication of Lu et al shows that a direct and current electrical field improves the wound healing ability in an experimental setting with human epidermal cells [ 4 ]. The migration and proliferation of cells exposed to electrical fields increased significantly compared to control group.…”
mentioning
confidence: 99%